The power at the end of the economy - Massumi, Brian (Duke University Press, 2015)
In his latest book, the influential critic Brian Massumi offers a new theory of political economy that demonstrates how emotional, affective and nonconscious decisions work together with rational self-interest in the shaping of neoliberalism. Massumi's analysis shows the potential for a new anti-capitalist politics.